The theses for MD degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
A.P. Schyokotova — Clinical and laboratory parameters and endothelial dysfunction at liver diseases, their diagnostic, prognostic value and potential of application for treatment response rate ratingA.A. Kurbatova — Pathogenic and clinical value of cytokine and claudin system at irritable bowel syndromeYe.N. Baranova — Liver cirrhosis: prognostic value of clinical and autonomous nervous system parametersV.L. Mel'nikov — State of the gut in HBsAg carriers and its correction by nonpharmacological methods (clinical, functional, morphological study)